(3TPhQ GdYbhO aj JGQjN GdYghOs - (3YHO GdQMef Hf Ydj Hf eMeO GdLhRj GdbQTj GdHZOGOj, CHh GdaQL, GHf GdLhRj , J (B597 (3g` s ((3EHQGgje Hf eMeO Hf EHQGgje GdeTghQ HGHf GdUGQe GdTGaYi s)
(3ChdgG (B:s
(3GdMeO ddg LdHi Ydi GdacQ eG Ldi ef GdYHQ s
(3BNQgG (B:s
(3hai GdchaI eGFI QWd JeQ HbjQGW hMHI hQNUJ GdahGcg s
(3fHPI UZjQI ai UaMI hGMOI efbhdI ef cJGHs
(3cTa GdfbGH Yf GdCSeGA hGdCdbGH dGHf GdLhRi Hjf ajgG Cf GdCSeGA ehVhYI ddJYQa Xf hGdCdbGH ehVhYI ddJTQjas
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B316 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B157 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B520s
Keywords: (3GdJGQjNs